Neurological findings in patients with COVID-19: a systematic review - Mawaddah Ar Rochmah; Sekar Satiti; Ismail Setyopranoto; Indra Sari Kusuma Harahap; Desin Pambudi Sejahtera; Dhite Bayu Nugroho; Sri Sutarni (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Since the emerging of the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection in Wuhan, China at the end of 2019, the coronavirus disease 2019 (COVID-19) has become pandemic for months. Due to fast increased number of the positive patients with COVID-19, SARS-CoV-2 is considered highly pathogenic virus with various clinical presentations. Apart from the typical respiratory symptoms, neurological complains in COVID-19 involving central and peripheral nervous systems have been reported. This paper aimed to review the neurological findings reported in patients with COVID-19. We qualitatively reviewed studies reporting COVID-19 patient(s) with neurological manifestations according to the recommendations of PRISMA statement.There were twelve studies included in this brief review. We found that patients with neurological findings were reported ranging from symptomatic complain of headache and dizziness to specific neurological diseases/syndromes, such as meningitis/encephalitis, acute cerebrovascular diseases, Guillain-Barré syndrome, and Miller Fisher syndrome. This review suggests the possible neurological involvement in COVID-19. We hope to raise the awareness of the health workers in taking care of the patients with COVID-19 and neurological diseases.